Null variants in DYSF result in earlier symptom onset. Issue 3 (8th February 2021) - Park, Hyung Jun; Hong, Young Bin; Hong, Ji‐Man; Yun, UnKyu; Kim, Seung Woo; Shin, Ha Young; Kim, Seung Min; Choi, Young‐Chul
Abstract: We investigated the clinical, laboratory, and genetic spectra in Korean patients with dysferlinopathy to clarify its genotype–phenotype correlation. We retrospectively reviewed 101 patients from 96 unrelated families with pathogenic variants of DYSF . The most common initial phenotype was Miyoshi myopathy in 50 patients. Median ages at examination and symptom onset were 23 [interquartile range (IQR): 18–30] and 36 years [IQR: 27–48], respectively. We observed 38 variants, including nine novel variants. Four variants (c.2494C > T, c.1284 + 2 T > C, c.663 + 1G > C, and c.2997G > T) in DYSF accounted for 62% of total allele frequencies of pathogenic variants. To analyze the genotype–phenotype correlation, we compared the clinical phenotype between patients with null/null (N/N; n = 55) and null/missense variants (N/M; n = 35). The N/N group had an earlier symptom onset age (median: 20 years [IQR: 17–25]) than the N/M group (median: 29 years [IQR: 23–35], p < .001). Total manual muscle testing scores in lower extremities were lower in the N/N group (median: 80 [IQR: 56–92]) than in the N/M group (median: 89 [IQR: 78–98], p = .013). Our study is the first to report that null variants in DYSF result in an earlier symptom onset than missense variants. Abstract :